Michael L. Morgan : history and moral normativity - Morgan, Michael L., 1944- (Library of Contemporary Jewish Philosophers, 2018)
Michael L. Morgan is an Emeritus Chancellor Professor at Indiana University and the Senator Jerahmiel S. and Carole S. Grafstein Visiting Chair in Jewish Philosophy at the University of Toronto. On the faculty of Indiana University for his entire career, he has also held Visiting Professorships at the Australian Catholic University, Northwestern University, Princeton University, Stanford University, and Yale University. A historian of philosophy informed by the continental and analytic philosophical traditions, Morgan has reflected on the key challenge of our day: how is objectivity possible in light of the historicity of human life? An interpreter of both "Athens" and "Jerusalem," Morgan has written on ancient Greek philosophy, modern Jewish philosophy, post-Holocaust theology and ethics, Zionism, and Messianism.